(REVIEW) Benjamin R. Barber, If Mayors Ruled The World: Dysfunctional Nations, Rising Cities, Warszawskie Wydawnictwo Literackie Muza SA, Warszawa 2014, pp. 480 - Pięta, Piotr (Political Preferences, 2016)
.